«Con l’uno pace, et con l’altro tregua, et con l’altro guerra»: dynamics of conflict and networks of agreements in late medieval Italy (Edad Media. Revista de Historia, 2024)
This article examines the methods of political and military conflict resolution in late medieval Italy. The recent renewal of studies of the history of political power and diplomacy in the peninsula between the Middle Ages and the Early Modern Age has in fact led to a more accurate consideration of the cohabitation of phases of conflict and phases of negotiation and the study of their change over time. The investigation focuses in particular on two case studies, two late 14th century treaties, and the Italic League and its renewals from 1455 onwards.
Keywords: Italy; late middle ages; diplomacy; war; correspondences; treaties